2012
DOI: 10.1590/s1807-03022012000300006
|View full text |Cite
|
Sign up to set email alerts
|

Numerical solution of coupled mass and energy balances during osmotic microwave dehydration

Abstract: Abstract. The mass and energy transfer during osmotic microwave drying (OD-MWD) process was studied theoretically by modeling and numerical simulation. With the aim to describe the transport phenomena that occurs during the combined dehydration process, the mass and energy microscopic balances were solved. An osmotic-diffusional model was used for osmotic dehydration (OD). On the other hand, the microwave drying (MWD) was modeled solving the mass and heat balances, using properties as function of temperature, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…It is observed that there is an effect due to the microwave oven power on the final value of the mass in the drying, as it is evident that at a similar temperature on the leaves (70°C), a lower value is obtained in its final mass due to the increase in power from 100 to 400 W; this does allow to show the effects of microwave power on drying (Dadalı et al, 2007;Feng et al, 2012;Hemis et al, 2011;Hill & Marchant, 1996). (Arballo et al, 2010(Arballo et al, , 2012Feng et al, 2012;Halder & Datta, 2012).…”
Section: Macro-kinetic Analyses Of the Drying Processmentioning
confidence: 94%
“…It is observed that there is an effect due to the microwave oven power on the final value of the mass in the drying, as it is evident that at a similar temperature on the leaves (70°C), a lower value is obtained in its final mass due to the increase in power from 100 to 400 W; this does allow to show the effects of microwave power on drying (Dadalı et al, 2007;Feng et al, 2012;Hemis et al, 2011;Hill & Marchant, 1996). (Arballo et al, 2010(Arballo et al, , 2012Feng et al, 2012;Halder & Datta, 2012).…”
Section: Macro-kinetic Analyses Of the Drying Processmentioning
confidence: 94%
“…Crank-Nicolson finite difference method was used for solving the final equation system. In stage 2 moisture content for each time step was calculated using equation 7 (Arballo et al, 2012b). The numerical solution to obtain temperatures and moisture profiles were coded in Matlab 7.2 (Mathworks, Natick, MA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Spiazzi and Mascheroni () developed a mathematical model for solute transfer that considered the tissue characteristics, the product geometry, the osmotic solution and the osmotic solution‐to‐product mass ratio. Arballo and other () used the model of Spiazzi and Mascheroni () to represent the OD of pear, by considering, in the equation, the solute transfer through the cell membranes and between intercellular spaces.…”
Section: Introductionmentioning
confidence: 99%